2019
DOI: 10.1371/journal.pone.0219136
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal measurement invariance of the Child Problematic Trait Inventory in older Chinese children

Abstract: The Child Problematic Traits Inventory (CPTI) is a newly developed informant-rated instrument to measure psychopathic traits during early childhood. The aim of this study was to examine the longitudinal measurement invariance of the CPTI in a group of Chinese schoolchildren. Mothers of 585 children aged 8 to 12 years (50% girls) completed the CPTI twice with one-year interval. Confirmatory factor analyses showed that the CPTI had strict invariance (i.e., equality of factor patterns, loadings, intercepts, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The CPTI consists of 28 items that are rated by the preschool, kindergarten, or grade school teacher of a child. Studies have demonstrated that the psychometric properties of the CPTI are adequate both in teacher-rated (e.g., Colins, Fanti, Larsson, et al, 2017; López-Romero et al, 2018) and parent-rated scores (e.g., Luo et al, 2019; Somma et al, 2016; Wang et al, 2018).…”
Section: Youth Psychopathy Measuresmentioning
confidence: 99%
“…The CPTI consists of 28 items that are rated by the preschool, kindergarten, or grade school teacher of a child. Studies have demonstrated that the psychometric properties of the CPTI are adequate both in teacher-rated (e.g., Colins, Fanti, Larsson, et al, 2017; López-Romero et al, 2018) and parent-rated scores (e.g., Luo et al, 2019; Somma et al, 2016; Wang et al, 2018).…”
Section: Youth Psychopathy Measuresmentioning
confidence: 99%
“…Firstly, descriptive statistics of the Grit-S scores were performed with SPSS 22.0 (IBM Corp, 2013). Next, following the previous longitudinal studies (e.g., Wang et al, 2012;Luo et al, 2019), the CFA with Mplus 7 Muthén, 1998-2015) was used to test LMI across time. The proposed two first-order factors structure was seen as a baseline model.…”
Section: Data Analysis Strategymentioning
confidence: 99%
“…This proposition has been increasingly acknowledged in recent years. For example, recent youth research has examined factorial invariance over time for different measurements, such as the "Problematic Trait Inventory" [37], the "Short Grit Scale" [38], and the "Center for the Epidemiological Studies Depression Scale" (CES-D) [32,33]. Specifically, the longitudinal invariance of the CES-D ensures that any changes derived from the scale between different time points are attributable to over-time development rather than structural instability in measurement [33].…”
Section: Plos Onementioning
confidence: 99%